The significance of international symposia on biomechanics and medicine in swimming - a multidisciplinary approach - Ungerechts, B. E.; Keskinen, K. L. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The authors, as contemporary witnesses of former BMS symposia recall some selected research approaches from the past decades of the Symposia. Papers by e.g. Miyashita (1999), Clarys (2006), Barbosa et al (2010) or Vilas-Boas (2014) drew attention to research work that might still be inspiring today, even in the context of our knowledge of current research contributions. In the period between BMS 01 (1970) and BMS 08 (1998), there were much fewer international scientific journals than today, and the accumulation of scientific knowledge related to art of swimming was slow and spread to literary sources of parent disciplines. At that time, the impetus for the training came mostly from land-based sports, which was considered unsatisfactory due to the lack of reference to locomotion in water. Among sport scientists attracted by swimming from e.g. biomechanics, movement analysis, exercise physiology, medical sciences and even psychology, a collective will was apparent that there is a need for a meeting point, a symposium, where exchanges of scientific knowledge is made possible. Proceedings of the symposium, after peer review, a la longue would contribute to the improvement of performance in competitions aswell. Simultaneously, it was Zeitgeist worldwide to "bridge the gap" and it is likely that this attitude is one of the secrets, why BMS is still vivid today after 12 symposia. Nearly 50 years after the start of the international symposia, currently known as Biomechanics and Medicine in Swimming (BMS), the seniors of the event share their mutual view on the evolution of various research fields. It is the aim of this paper to lead the reader to explore what have been gained by the Series of BMS Symposia during the past nearly five decades. The original scientific articles have been printed in Proceedings and archived in an electronic database for openly accessible to anybody interested to read. Scientific discussions occur at the time of each Symposium but there is also space for science communication which we intend to stimulate by this article.